LA HUELGA FERROVIARIA EN COSTA RICA Y LA NACIONALIZACIÓN DE LA EMPRESA DEL FERROCARRIL AL ATLÁNTICO (1972) - Botey Sobrado, Ana María (2007)
The article analyzes the historical processes that led to both the consolidation and decline of popular workers’ movements. Here, the author uses as an example the case of the railway company in the Costa Rican Caribbean region. The work seeks to resurface the various theoretical considerations regarding social movements, to subsequently characterize the national and international context at the moment of the railroad’s nationalization, the current development trends, and the role of the companies that ran the railroads, going on to discover and establish the various dynamics that made possible the consolidation, in first place, and later, the decline of the railroad movement in the Caribbean region.